The association between visceral adiposity index and long-term all-cause mortality shows age-related disparities: a nationwide cohort study - Qiushi Sun; Sibo Wang; Xudong Han; Lingfeng Gu; Hao Wang; Qin Yang; Liansheng Wang (BMC Public Health)
Abstract Background The prevalence of obesity has increased rapidly worldwide over the past few decades and remains a recognized public health concern. However, studies exploring visceral adiposity index (VAI), a sex-specific indicator reflecting visceral fat distribution and function, and long-term mortality are limited. This study aimed to investigate the association of VAI with long-term all-cause mortality among general adults in the United States. Methods This cohort study used data from the National Health and Nutrition Examination Survey (NHANES) 1999–2018. Participants were linked to National Death Index mortality data through December 31, 2019. Weighted Cox proportional hazards regression model was used to calculate hazard ratios (HRs) and 95% CIs, and restricted cubic spline (RCS) was also conducted. Results A total of 21,943 US adults (weighted mean age, 46.9 years; 10,921 males [weighted, 49.1%]) were included. During 211,473 person-years of follow-up (median follow‑up: 9.3 years), 3326 total deaths occurred. After multivariable adjustments, compared with the 3rd quintile (Q3) of VAI, participants in the 2nd (Q2) and 5th (Q5) quintiles were at a significantly higher risk of all-cause mortality (HR 1.16 [95% CI, 1.00-1.34] and HR 1.15 [95% CI, 1.01–1.31], respectively). RCS revealed a U-shaped relationship of log2-transformed VAI to all-cause mortality (P for nonlinearity < 0.001), with an inflection point of 0.824. Subgroup analysis indicated that there was a significant interaction of VAI with age on all-cause mortality (P for interaction = 0.005). Higher VAI levels were associated with higher all-cause mortality in younger adults (Q5 vs. Q3, HR 1.56 [95% CI, 1.12–2.18], P = 0.009) rather than older adults (Q5 vs. Q3, HR 1.05 [95% CI, 0.91–1.22], P = 0.497). Conclusions In the nationally representative cohort of US adults, VAI was nonlinearly associated with long-term all-cause mortality and the association showed age-related disparities. A higher VAI was related to a higher mortality risk in younger adults. These findings underscore the importance of appropriate VAI for long-term health outcomes, especially for young adults.